1979
DOI: 10.3758/bf03209670
|View full text |Cite
|
Sign up to set email alerts
|

Licking one saccharin solution for access to another in rats: Contingent and noncontingent effects in instrumental performance

Abstract: Separation of the contingent and noncontingent effects of a schedule on amount of instrumental responding is desirable but difficult in schedules that involve instrumental and contingent responses that are either highly probable or very similar. Three studies in which rats were required to lick a solution of .1% saccharin for access to a preferred solution of .4% saccharin showed that neither single nor paired operant baselines of the instrumental response allowed accurate separation of the contingent and nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…In summary, the results of this experiment suggest the sufficiency of the state of response deprivation to produce reinforcement effects in an academic context, thereby systematically replicating basic laboratory research findings (Allison et al, 1979; , 1975Bernstein, 1974;Eisenberger et al, 1967;Heth & Warren, 1978;Timberlake, 1979;Timberlake & Wozny, 1979). However, because of the tentative nature of the effects of the MC conditions, it cannot be determined how much of the increases in the instrumental responding were due to the contingent relationship between the responses.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…In summary, the results of this experiment suggest the sufficiency of the state of response deprivation to produce reinforcement effects in an academic context, thereby systematically replicating basic laboratory research findings (Allison et al, 1979; , 1975Bernstein, 1974;Eisenberger et al, 1967;Heth & Warren, 1978;Timberlake, 1979;Timberlake & Wozny, 1979). However, because of the tentative nature of the effects of the MC conditions, it cannot be determined how much of the increases in the instrumental responding were due to the contingent relationship between the responses.…”
Section: Resultssupporting
confidence: 72%
“…The fact that Dave's increased coloring behavior was maintained in the MC condition may suggest that deprivation alone (without contingency) may be sufficient to achieve a reinforcement effect. It may be that true instrumental conditioning did not underlie the reinforcement effect; rather, the removal of the contingent response alone may have produced this result in the RD conditions (Bernstein & Ebbeson, 1978;Timberlake, 1979). However, certain methodological limitations in the use of the MC condition in the present study are relevant to this issue.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Some studies have shown that mere restriction of one response in a pair is sufficient to produce an increase in the other response, independent of any contingent relation (e.g., Allison & Timberlake, 1974;Bernstein, 1974;Dunham, 1972; Timberlake, 1979). Few studies, however, have restricted access to one response and examined the effects on two or more other responses (Dunham, 1977;Knapp, 1976; Konarski, Crowell, Johnson, & Whitman, 1982;Konarski, Johnson, Crowell, & Whitman, 1981; but see, e.g., Lyons & Cheney, 1984;Rojahn, Mulick, McCoy, & Schroeder, 1978).…”
mentioning
confidence: 99%